2022
DOI: 10.1590/2675-2824070.22137jgp
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of chemoautotrophy and heterotrophy to the microbial carbon cycle in the Southwestern Atlantic Ocean

Abstract: Dark carbon fixation (DCF) is a source of new and labile carbon in the deep ocean, while heterotrophic microbial production (HMP) promotes organic matter transfer through the microbial loop. Despite their ecological relevance, there is a scientific gap regarding the estimates of DCF and HMP in the Southwestern Atlantic Ocean. Thus, the aim of this study was to investigate the spatial distribution of DCF and HMP; their relevance to the ocean carbon cycle; their relationship with environmental parameters and amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
(115 reference statements)
1
2
0
Order By: Relevance
“…Chemosynthesis has also been reported to be higher and more variable in mesopelagic compared to bathypelagic zones (Reinthaler et al, 2010); however, the rates in this study were homogeneous between pelagic zones. Our results corroborate those of Li et al (1993) for the North Atlantic and Sargasso Sea and of Passos et al (2022) for the Santos Basin upper slope, where oceanic chemoautotrophy did not vary with depth. Farías et al (2009) found that, on average, chemosynthetic production was divided equally in the euphotic and aphotic layers, suggesting that dark carbon fixation can be crucial in euphotic zones, the usual established realm of photosynthesis.…”
Section: Chemoautotrophysupporting
confidence: 88%
See 2 more Smart Citations
“…Chemosynthesis has also been reported to be higher and more variable in mesopelagic compared to bathypelagic zones (Reinthaler et al, 2010); however, the rates in this study were homogeneous between pelagic zones. Our results corroborate those of Li et al (1993) for the North Atlantic and Sargasso Sea and of Passos et al (2022) for the Santos Basin upper slope, where oceanic chemoautotrophy did not vary with depth. Farías et al (2009) found that, on average, chemosynthetic production was divided equally in the euphotic and aphotic layers, suggesting that dark carbon fixation can be crucial in euphotic zones, the usual established realm of photosynthesis.…”
Section: Chemoautotrophysupporting
confidence: 88%
“…Although the chemosynthetic rates in this study are the first that we are aware of in the spatial width of the Santos Basin, they are in the same order of Planktonic photo-and chemoautotrophy in Santos Basin Ocean and Coastal Research 2023, v71(suppl 3):e23006 13 Kutner et al magnitude as those found in the South Atlantic by Prakash et al (1991), which ranged from 0.17 to 3.81 mg C m -3 h -1 . Signori et al (2018) measured dark carbon fixation from 0.001 to 2.72 mg C m -3 h -1 in GB, and Passos et al (2022) reported rates between 0.02 and 0.3 mg C m -3 h -1 on the upper slope region of the basin. Farías et al (2009) measured high rates in the upwelling off the Chilean coast, varying between 0.2 and 145 mg C m -3 d -1 (0.008 -6.04 mg C m -3 h -1 ) in the euphotic zone and between 0.16 and 117 mg C m -3 d -1 (0.007 -4.87 mg C m -3 h -1 ) in the aphotic zone.…”
Section: Chemoautotrophymentioning
confidence: 99%
See 1 more Smart Citation